Should we legalize marijuana? Ten years of learning from JWH-018 first seizure. (29th March 2019) - Quintas, Alexandre
Abstract : Introduction: The medical use of cannabis predates history, finding its first historical root in ancient China 4700 years ago. The main psychoactive component of cannabis is Δ 9 -tetrahydrocannabinol (Δ 9 -THC) first isolated by Gaoni and Mechoulam [1 ]. In the 1960's Richard Nixon started a war on drugs both to control the internal US movements against Vietnam war and for racial reasons. In fact, citing JD Ehrlichman, Nixon assistant for domestic affairs, "getting the public to associate the hippies with marijuana and blacks with heroin and then criminalizing both heavily, we could disrupt those communities" [2 ]. Due to cannabis control by UN acts of 1961 and 1971, in the end of 70's Pfizer© and Lilly© start developing synthetic cannabinoids (SC) for clinical purposes [3 ]. SC have similar effects of Δ 9 -THC and cannabidiol, (CBD) presented in marijuana. JWH-018 a SC was synthetized by J.W.Huffman in 1995 as a drug to treat cancer [4 ]. This molecule was the active substances of herbal blends sold on smartshops, according to a report from the pharmaceutical company THC Pharm in 2008 [5 ]. After this almost 200 new SC have been reported by the early warning system of the EMCDDA [6 ]. The ugly true is that, in early years of XXI century, products containing SC have been sold in Europe and marketed as 'legal' replacements for cannabis. Moreover a 2009 survey conducted among 1463 students aged between 15 and 18 in Frankfurt found that around 6% of the students reported having used 'Spice' at least once [5 ]. New psychoactive substances (NPS) in general and SC in particular may pose health and social risks to our society that demands an open and scientific discussion about marijuana legalization. Materials and methods: A review was carried out on PubMed, EMCDDA and United Nations sites to gather scientific data about cannabis and SC effects on human health. Results: A study, from 1843, suggested that cannabis sativa "possess very striking powers as an antispasmodic, as a nervine stimulant, and as an anodyne and hypnotic, and in some respects to excel opium in virtue" [7 ]. 175 years after this report, studies on neurological uses of Δ 9 –THC and CBD reports positive outcomes on malignant brain tumors, Parkinson's, Alzheimer's, multiple sclerosis and neuropathic pain. In addition, psychiatric and mood disorders, such as schizophrenia, anxiety, depression, and posttraumatic stress also seem to benefit from the use of phytocannabinoids [8 ]. A great number of papers and clinical reports show that Δ 9 –THC and CBD is beneficial clinically. Actually, Dronabinol and Nabilone are two cannabinoids synthetized and commercialized by pharmaceutic industry with clinical usage. Discussion and conclusions: SC molecules appears in the street and internet market on a regular base. The new emerging molecules are slightly different from the previous to avoid legislation. This makes almost impossible to characterize new SC toxicological profiles on a sensible time scale. The control of marijuana have been having consequences on consume of SC with reported fatalities [9 ] which are absent in marijuana consume. Besides, control of cannabis sativa has strong consequences in scientific research. It is time to face scientifically the pros and cons of marijuana legalization for a conscious political decision.